2001
DOI: 10.1590/s0101-81752001000300010
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da fragmentação florestal sobre vespas e abelhas solitárias na Amazônia Central. II. estratificação vertical

Abstract: ABSTRACT. Effcets offorcst fragmcntatioo 00 solitary wasps aod bccs in Ccntral Amazonia. 11. VCI-tical stratifieation. The ef'fects oI' forest fragmentation on the pallerns ofvertical abundance and richness of'solilary wasp and bee communilies was investigated near Manaus, Amazonas. Wasps and bees were trap-nested at 1,5, 8and 15 mabove lhe ground in continuous primary forest and isolated forest fragments. Jn general, lhe numbel' oI' nests and species increased with height for both groups. In particular, bee s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
3
24
1
9
Order By: Relevance
“…Wooden pieces measured 25x25x130 mm and had 11 cm-deep canals with 6, 9, and 12 mm diameter. Trapnest sizes in this study are similar to those in other studies (Morato & Campos 2000, Morato 2001a. Ten wooden pieces of each canal diameter were randomly arranged as trap-nest blocks.…”
Section: Location Of Trap-nestsmentioning
confidence: 68%
See 1 more Smart Citation
“…Wooden pieces measured 25x25x130 mm and had 11 cm-deep canals with 6, 9, and 12 mm diameter. Trapnest sizes in this study are similar to those in other studies (Morato & Campos 2000, Morato 2001a. Ten wooden pieces of each canal diameter were randomly arranged as trap-nest blocks.…”
Section: Location Of Trap-nestsmentioning
confidence: 68%
“…Bawa et al (1985) reported that bigger bees are more important pollinators when flowers are located in the canopy. In the Central Amazon region, bees occupied more trap-nests located between 15 m and 8 m high than those at 1.5 m (Morato 2001a). This result may be due to a larger availability of floral resources in the canopy (Roubik et al 1982).…”
Section: Discussionmentioning
confidence: 94%
“…This variation, however, must be interpreted cautiously because, in addition to the potential diversity of species in the study area (ALVES-DOS-SANTOS 2003), the results can be affected by different man-made nesting materials (BOSCH 1995), trapnest diameter (VANDENBERG 1995), height of trap-nests in relation to ground level (MORATO 2001), exposure of trap-nests to sun (FRANKIE et al 1988), availabity of natural preexisting cavities , and by the period of sampling. Irrespective of these variables, some general patterns has emerged from the studies made.…”
Section: Species Richness and Abundancementioning
confidence: 99%
“…Some of the studies were made to obtain information on the nesting biology (KROMBEIN 1967, STRICKLER et al 1996, PEREIRA et al 1999, MORATO et al 1999, JESUS & GARÓFALO 2000, AGUIAR & GARÓFALO 2004, ZILLIKENS & STEINER 2004, whereas other provide information on population dynamics (JAYASINGH & FREEMAN 1980), preferred habitats (FRANKIE et al 1988, GATHMANN et al 1994, reproductive biology of parasites which hosts nest in trap-nests (SCOTT et al 2000, GAZOLA & GARÓFALO 2003 and composition and seasonal patterns of communities (CAMILLO et al 1995, GARÓFALO 2000, AGUIAR & MARTINS, 2002ALVES-DOS-SANTOS 2003). More recently, trap-nesting bees and wasps have been used in researches designed to evaluate the habitat quality (FRANKIE et al 1998, TSCHARNTKE et al 1998, the effects of habitat fragmentation and of the landscape complexity on community composition and predator-prey interactions (MORATO & CAMPOS 2000, MORATO 2001, STEFFAN-DEWENTER 2002, KRUESS & TSCHARNTKE 2002 asil. asil.…”
mentioning
confidence: 99%
“…Data on communities of trap-nesting bees and wasps and their natural enemies have been used in research on habitat quality (Frankie et al, 1998;Tscharntke et al, 1998), the effects of habitat fragmentation and of landscape complexity on community composition and predatory-prey interactions (Morato and Campos, 2000;Morato, 2001;Steffan-Dewenter, 2002;Kruess and Tscharntke, 2002;Klein et al, 2006;Tylianakis et al, 2006) and how urban environments can support such insects (Tommasi et al, 2004;Zanette et al, 2005).…”
Section: Introductionmentioning
confidence: 99%